2008
DOI: 10.2147/opth.s2305
|View full text |Cite
|
Sign up to set email alerts
|

The trabecular bypass stent in a pseudophakic glaucoma patient: A 1-year follow-up

Abstract: PurposeTo describe the 1-year success of a trabecular stent implant in a pseudophakic glaucoma patient. The stent is implanted through a small corneal incision under gonioscopic control. Intraocular pressure control was reported in cultured human anterior segment.DesignObservational case report.MethodsWe report the case of a patient who was implanted and followed-up for 1 year at the Dipartimento di Fisiopatologia Clinica. The main outcome measures were intraocular pressure and visual field.ResultsThe patient’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Fea et al . reported a single patient in whom pressure was lowered by implanting the iStent . Spiegel et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fea et al . reported a single patient in whom pressure was lowered by implanting the iStent . Spiegel et al .…”
Section: Introductionmentioning
confidence: 99%
“…Fea et al reported a single patient in whom pressure was lowered by implanting the iStent. 11 Spiegel et al reported six patients who underwent iStent implantation resulting in reduction of IOP and topical hypotensive medication use. 12 The aim of this study was to evaluate the safety and efficacy of the iStent in reducing IOP in a larger patient cohort with open-angle glaucoma in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…The same author previously published a case report demonstrating the effectiveness of the procedure in one pseudophakic patient. 13 More recently the effect of the iStent on flow was further elucidated by a fluorophotometic study by Fernandez-Barrientos et al 14 Thirty-three eyes of 33 patients were randomized to either two stents and cataract surgery (n = 17, Group 1) or cataract surgery alone (n = 16, Group 2). Before surgery, flow and outflow facility were similar between Groups 1 and 2 (1.78 +/-0.44 and 1.74 +/-0.82 microL/min; P = 0.18; 0.12 +/-0.03 and 0.13 +/-0.06 microL/min/mm H; P = 0.71, respectively).…”
Section: Istentmentioning
confidence: 99%